Functional Movement ScreenTM – Normative Values in Healthy Distance Runners - Agresta, C.; Slobodinsky, M.; Tucker, C. (International Journal of Sports Medicine, 2014)
Recreational runners have an estimated overuse injury incidence rate of up to 79% and 90% for marathoners. A pre-participation screening tool that can identify risk for injury may help reduce overuse injury in runners. The Functional Movement Screen (FMSTM) is a reliable clinical tool used with athletes to help predict injury. To date, the FMSTM has not been used with endurance athletes. The purpose of this article is to establish normative FMSTM values for distance runners. 45 healthy runners performed the FMSTM. Descriptive statistics were calculated; independent t-tests were performed to examine the effect of gender, experience and injury on scores. A Chi-square test was used to evaluate whether significant differences in scores exist for any component of the FMSTM. The mean FMSTM score was 13.13±1.8. No significant differences in FMSTM scores were found between novice and experienced runners (p=0.71) or runners with a history of injury and those without (p=0.20). While male and female runners did not differ significantly in their total FMSTM score (p=0.65), significant differences were found in the deep squat (p<0.05), trunk stability push-up (p<0.001) and active straight leg raise components (p=0.002). This study provides normative values for FMSTM scores when testing uninjured distance runners.
Keywords: functional movement; distance runners; injury